Redescription of Tetebius latibunus as a new senior synonym of Malgaceros boviceps (Opiliones: Laniatores: Biantidae) - Mamani, Vanesa; Pérez-González, Abel (Zootaxa, 2025)
The holotype of Tetebius latibunus Roewer, 1949, and the topotype material of Malgaceros boviceps Lawrence, 1959, were thoroughly examined and compared. No morphological differences were found between these specimens. Consequently, a new synonymy is herein proposed, identifying Malgaceros boviceps as a synonym of Tetebius latibunus, and subsequently, Malgaceros Lawrence, 1959, as a synonym of Tetebius Roewer, 1949. Additionally, the holotype of Tetebius latibunus is considered a minor male, whereas the junior synonym Malgaceros boviceps is considered as a major male. A revised description and detailed illustration of the species Tetebius latibunus are provided, based on a comprehensive review of the holotype and numerous specimens that were collected in Nosy Be, Madagascar, the type locality of Malgaceros boviceps. The original type locality attributed to Tetebius latibunus by Roewer (Tete, Mozambique) is now believed to be a mislabeling, and the species is considered endemic to Madagascar.